"Da upanishad : short discourse on self-renunciation, God-realization and the illusion of relatedness" - Da Love - Ananda (California, 1989)
Heart-Master Da Love-Ananda Appears as a man, but He is no more confined to His physical frame than the light of the stars is attached to their surface. He is in fact the unobstructed Embodiment of the very Divine Existence That is worshipped in every Sacred Tradition, and under many ames. In THE DA UPANISHAD Heart-Master Da Reveals His essential Wisdom- Arguments and fundamental disciplines that will, by His Graceful Blessing, enable "even the least qualified of living beings" to Awaken to the Eternal Divine Self. In these concentrated and sublime essays, He Offers an unsurpassed description of both the precise mechanism of delusion and the nature, process, and ultimate fulfillment of Transcendental Divine Realization .
Keywords: Spiritual life